The change of depository of a collection of scale insects by Ryoichi Takahashi (Hemiptera: Sternorrhyncha: Coccomorpha) - Williams, Douglas J. (Zootaxa, 2017)
Ryoichi Takahashi (1898–1963) was a Japanese entomologist with considerable expertise on the Sternorrhyncha of the Far East and southern Asia. Most of his early articles were in Japanese, the first being published in 1916; but later he also wrote many articles in English. At first he published mainly on aphids (Aphidomorpha) and whiteflies (Aleyrodomorpha). His first article on scale insects did not appear until 1928, describing species from Formosa (Taiwan), where he worked at the Government Agricultural Research Institute. He produced a further 73 articles on scale insects (García et al. 2017). In total, he published almost 420 articles according to Ito and Sorin (1963).